2019
DOI: 10.17921/2447-8938.2019v21n2p108-111
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Odontogenic Keratocyst with Application of Carnoy's Solution: Case Report

Abstract: Odontogenic cysts are benign non-neoplastic lesions that originate from epithelial cells Arachnida-Araneae) community in the process of the teeth development. Among them, the odontogenic keratocyst is a developmental cyst characterized by its epithelium of parakeratinized stratified and aggressive squamous cells as well as infiltrative behavior. Thus, the objective of this study was to describe a clinical case of surgical treatment of odontogenic keratocysts in a 52-year-old female patient, who presented for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the past, opioid drugs were mainly selected in traditional clinical analgesia, although they have good analgesic effect, but they also have many side effects. It is easy to lead to respiratory depression and immune dysfunction and other complications [17] . Dickson E L et al [18] reported that opioids can increase the risk of postoperative intestinal obstruction to some extent, so reducing the use of opioids can help to reduce the incidence of postoperative complications.…”
mentioning
confidence: 99%
“…In the past, opioid drugs were mainly selected in traditional clinical analgesia, although they have good analgesic effect, but they also have many side effects. It is easy to lead to respiratory depression and immune dysfunction and other complications [17] . Dickson E L et al [18] reported that opioids can increase the risk of postoperative intestinal obstruction to some extent, so reducing the use of opioids can help to reduce the incidence of postoperative complications.…”
mentioning
confidence: 99%